Pharmacological inhibition of BAG3‐HSP70 with the proposed cancer therapeutic JG‐98 is toxic for cardiomyocytes. Issue 1 (6th September 2021) - Martin, Thomas G.; Delligatti, Christine E.; Muntu, Nitha Aima; Stachowski‐Doll, Marisa J.; Kirk, Jonathan A.
Abstract: The co‐chaperone Bcl2‐associated athanogene‐3 (BAG3) maintains cellular protein quality control through the regulation of heat shock protein 70 (HSP70). Cancer cells manipulate BAG3‐HSP70‐regulated pathways for tumor initiation and proliferation, which has led to the development of promising small molecule therapies, such as JG‐98, which inhibit the BAG3‐HSP70 interaction and mitigate tumor growth. However, it is not known how these broad therapies impact cardiomyocytes, where the BAG3‐HSP70 complex is a key regulator of protein turnover and contractility. Here, we show that JG‐98 exposure is toxic in neonatal rat ventricular myocytes (NRVMs). Using immunofluorescence microscopy to assess cell death, we found that apoptosis increased in NRVMs treated with JG‐98 doses as low as 10 nM. JG‐98 treatment also reduced autophagy flux and altered expression of BAG3 and several binding partners involved in BAG3‐dependent autophagy, including SYNPO2 and HSPB8. We next assessed protein half‐life with disruption of the BAG3‐HSP70 complex by treating with JG‐98 in the presence of cycloheximide and found BAG3, HSPB5, and HSPB8 half‐lives were reduced, indicating that complex formation with HSP70 is important for their stability. Next, we assessed sarcomere structure using super‐resolution microscopy and found that disrupting the interaction with HSP70 leads to sarcomere structural disintegration. To determine whether the effects of JG‐98 could be mitigated by pharmacological autophagy induction, we cotreated NRVMs with rapamycin, which partially reduced the extent of apoptosis and sarcomere disarray. Finally, we investigated whether the effects of JG‐98 extended to skeletal myocytes using C2C12 myotubes and found again increased apoptosis and reduced autophagic flux. Together, our data suggest that nonspecific targeting of the BAG3‐HSP70 complex to treat cancer may be detrimental for cardiac and skeletal myocytes. Abstract :